Career transition of middle-aged professionals - Anderson, Mafalda Maria de Medeiros; Veloso, Elza Fátima Rosa; Trevisan, Leonardo Nelmi; Stefani, Silvio Roberto (Revista de Administração da UFSM, 2021)
Purpose – This article analyzes the career transition of middle-aged professionals, according to three factors: identity transition, transition drivers and resources triggered in transition. Design/methodology/approach – Qualitative research, developed from semi-structured interviews with professionals between 35 and 54 years old. Content analysis was used in the evaluation categories and in the definition of the interview categories. Findings – It was demonstrated, in part by the interviewees, the construction of expectations that alternated the accomplishment of a dream, with cycles of anguish, especially for the financial aspects involved. The subjective factors of the transition process appeared in the interviews, both due to the conflict between the search for personal satisfaction in the new career and the safety flow of the previous one, as well as the complex balance between personal and professional life during the transition. Research limitations/implications – The sampling has no mathematical or statistical basis, preventing the generalization of its results. A quantitative study is recommended to understand how the transition occurs in middle-aged professionals, analyzing a large number of respondents. Practical implications – For middle-aged professionals, this study suggests the need for planning in the career transition phase and the assimilation of the self-management logic as a definitive career dynamic. Social implications - Companies must recognize the impact of career transitions on retaining professionals. Originality/value - This article contributes on the elucidation of the main drivers and resources available for the career transition of middle-aged professionals.